Different Dimensions of Affective Processing in Patients With Irritable Bowel Syndrome: A Multi-Center Cross-Sectional Study - Berens, Sabrina; Schaefert, Rainer; Ehrenthal, Johannes C.; Baumeister, David; Eich, Wolfgang; Tesarz, Jonas (Frontiers in Psychology, 2021)
Objective: Deficits in affective processing are associated with impairments in both mental and physical health. The role of affective processing in patients with functional somatic complaints such as irritable bowel syndrome (IBS) remains unclear. Most studies have focused on the capacity for emotional awareness and expression, but neglect other dimensions of affective processing. Therefore, this study aimed to systematically analyze differences in six different dimensions of affective processing between patients with IBS and healthy controls (HCs). Additionally, we exploratively investigated the impact of IBS symptom severity, psychological distress and attachment styles on affective processing in IBS. Methods: A controlled cross-sectional multi-center study was conducted. Overall, 127 patients with IBS were compared with 127 matched HCs using multivariate analysis of variances. Affective processing was operationalized in line with the affect cascade model on six specific dimensions: emotional experience, emotional awareness, affect tolerance, affect differentiation, affect regulation, and emotional communication. They were measured using two subscales of the Mentalizing Questionnaire (MZQ) and four subscales of the Operationalized Psychodynamic Diagnosis - Structure Questionnaire (OPD-SQ). Linear regression analysis was used to investigate the influence of IBS symptom severity (IBS-Symptom Severity ScaleSeverity Scoring System, IBS-SSS), depression (Patient Health Questionnaire, PHQ-9), anxiety (General Anxiety Disorder, GAD-7), and anxious and avoidant attachment styles (Experiences in Close Relationships Scale, ECR-RD12) on the different dimensions of affective processing in IBS. Results: Patients with IBS compared to HCs showed deficits in all six dimensions of affective processing. Deficits were largest for affect tolerance (d=.849) and lowest for emotional experience (d=.222) and emotional awareness (d=.420). Moderate effect sizes were found for affect differentiation (d=.773), emotional communication (d=.665), and affect regulation (d=.552). Moreover, explorative analyses indicated that affective processing in patients with IBS was significantly influenced by levels of anxiety and insecure attachment. Conclusion: The results indicate a specific pattern of affective processing abilities in patients with IBS. The deficits in affective processing are more prominent in the area of understanding and tolerating difficult affective states than experiencing affective states. This opens interesting perspectives for the development of specific psychotherapeutic interventions. Trail Registration: DRKS00011685